A Facile Synthesis and Optical Properties of Bundle-Shaped TbPO4·H2O Nanorods - Dan Yue; Wen Luo; Wei Lu; Ruiyong Wang; Chunyang Li; Jiazhong Chang; Zhenling Wang (Advances in Condensed Matter Physics)
Bundle-shaped TbPO4·H2O nanorods have been prepared by a facile hydrothermal technique and characterized by XRD, SEM, TEM, UV-Vis diffuse reflectance spectrum (DRS), photoluminescence (PL) spectrum, and lifetime. The results indicate that the obtained sample has hexagonal structure of TbPO4·H2O and is composed of nanorods bundles which is assembled from many single crystalline nanorods with the diameter of around 45 nm and the length of 2.3 μm. The growth of the single crystalline nanorod is along the (001) plane direction. Under the UV light irradiation, TbPO4·H2O nanorods bundles exhibit bright green emission corresponding to the D54→F7J (J=6,5,4,3) transitions of the Tb3+ ions, and the lifetime is determined to be about 0.24 ms.